Distribution of urinary hippuric acid concentrations by ALDH2 genotype. Issue 12 (December 1994) - Kawamoto, T; Murata, K; Koga, M; Hattori, Y; Kodama, Y
Abstract : OBJECTIVES–To clarify the relation between the genetic polymorphism of ALDH2 (low Km aldehyde dehydrogenase) and toluene metabolism. METHODS–The study subjects were 253 toluene workers (192 men and 61 women with an age range of 18-66). The genotypes of ALDH2 were classified by artificial restriction fragment length polymorphism into the homozygous genotype of normal ALDH2 (NN), the homozygous genotype of an inactive ALDH2 (DD), and the heterozygous genotype of normal and inactive ALDH2 (ND). The concentrations of hippuric acid (HA), the main metabolite of toluene, was determined in urine specimens of 253 toluene workers. The HA measurements in previous occupational health examinations were also referenced. The HA concentrations corrected for creatinine (HA/C) were compared with the biological exposure index (BEI) for toluene, which is 2.5 g/g creatinine. To estimate the toluene exposures, urinary o-cresol concentrations were also determined and compared with another BEI for toluene–that is, 1.0 mg urinary o-cresol/g creatinine. RESULTS–Incidence of each genotype in the toluene workers was almost the same as that in non-exposed controls who lived in the same area as the toluene workers. The incidence of each of the three genotypes also did not differ by smoking habit. Mean urinary HA concentrations were not significantly different in the groups with the different genotypes of ALDH2. The HA concentrations of > 70% of the 890 total samples were < 1.0 g/l. The number of urine samples > 3.0 g/l was 28 (5.4%) in the NN group and 19 (6.4%) in the ND group. No urine samples in the DD group were > 3.0 g/l HA. The distribution of urinary HA in the DD group was significantly different from those in both the NN and ND groups (P < 0.05). Seven (4.9%) of the 136 total specimens in the NN group and four (4.7%) of the 82 total specimens in the ND group exceeded the BEI. There were, however, no urine specimens that exceeded the BEI in the DD group. The maximum HA concentration after correction for creatinine in the DD group was 1.86 g/g creatinine. The percentages of urine specimens in which o-cresol concentrations exceeded this BEI were 14.3% in the NN group, 9.1% in the ND group, and 15.4% in the DD group. Therefore, the exposure rate for all three genotypic groups of workers was almost the same. CONCLUSIONS–The HA concentrations of toluene workers with ALDH2 DD genotype were lower than those of the NN and ND genotypes when they were exposed to relatively high concentrations of toluene. The exposures of the DD group were suspected to be underestimates because they were based on the BEI for the NN genotype.